Major depression disorder - etiology and treatment - Paulina Czuchryta; Rafał Babiak; Karolina Bajak; Anastazja Domańska; Agnieszka Gawęda; Agata Grabek; Julia Rutkowska; Żaneta Rzęsa-Tokarczyk; Klaudia Skorek; Agnieszka Urbańczyk (Kazimierz Wielki University, 2023)
Introduction and purpose: The problem of major depression disorder (MDD) affects more and more people. In a few years, it may become the most common disease after cardiovascular diseases and cancer. MDD are manifested by a depressed mood, decreased energy, loss of interest and the ability to enjoy life, as well as a number of other additional symptoms. Untreated MDD can lead to disability. This entails not only consequences for the sick person but also increased social costs. That is why it is so important to know the causes of its formation and to look for new therapeutic methods. State of knowledge: The development of MDD is influenced by genetic factors, inflammatory factors and hormonal disorders, changes in the structure of the brain, disorders in neurotransmission. The microbiome-gut-brain axis affects mood regulation and neurotransmission in the brain. Bacteria such as Escherichia, Shigella, Enterococcus, Streptococccus, Alistipes, Parabacterioides, Veillonella have been identified as having a potential negative effect on the development of MDD and response to treatment. The use of probiotics containing Lactobacillus helveticus R0052, Bifidobacterium longum and Clostridium butyricum MIYAIRI 588 may help reduce the symptoms of MDD. In recent years, the US Food and Drug Administration (FDA) has approved the intranasal preparation of esketamine for the treatment of treatment-resistant depression and major depressive disorder with severe suicidal thoughts. Unlike other antidepressants, it has a quick effect on reducing symptoms. Summary: Due to the global problem of MDD, further research is needed to better understand the mechanisms of its formation. Particular attention should be paid to the influence of microbiota.